Business Cycle Phases in U.S. States - Owyang, Michael T.; Piger, Jeremy; Wall, Howard J. (The Review of Economics and Statistics, 2005)
The U.S. aggregate business cycle is often characterized as a series of distinct recession and expansion phases. We apply a regime-switching model to state-level coincident indices to characterize state business cycles in this way. We find that states differ a great deal in the levels of growth that they experience in the two phases: Recession growth rates are related to industry mix, whereas expansion growth rates are related to education and age composition. Further, states differ significantly in the timing of switches between regimes, indicating large differences in the extent to which state business cycle phases are in concord with those of the aggregate economy. © 2005 President and Fellows of Harvard College and the Massachusetts Institute of Technology.